Community pond rehabilitation to deal with climate variability: a case study in Nepal Terai - Bastakoti, Ram C.; Prathapar, Sanmugam A.; Okwany, Romulus O. (Elsevier, 2016)
A large number of small- to medium-sized community ponds exist in most parts of the Terai region in Nepal. Such ponds could be a viable alternative for other forms of surface irrigation. But, with the lack of efficient management, many of these ponds remain underutilized. An effort was made to facilitate the rehabilitation of such a pond in a selected village of Rupandehi District in Western Terai region of Nepal. This paper aims to evaluate the changed water availability situation in post-monsoon seasons after the pond rehabilitation. The paper also evaluates the feasibility of such interventions especially focusing on the potential to provide additional water and improve agricultural productivity. Results showed small increases in quantifiable indicators such as water availability, cropping intensity, productivity and income. The new institutional setup improved water allocation, improved operation and maintenance, and increased social awareness among the people about the importance of underutilized water resources. The intervention has the potential to be replicated in similar contexts.